From Eton to Ypres : the letters and diaries of Lt Col Wilfrid Abel Smith, Grenadier Guards, 1914-15 /: the letters and diaries of Lt Col Wilfrid Abel Smith, Grenadier Guards, 1914-15. (2016) - Smith, Wilfrid Abel, 1870-1915
No abstract available